Polymerizable Ionic Liquid-Based Gel Polymer Electrolytes Enabled by High-Energy Electron Beam for High-Performance Lithium-Ion Batteries - Wookil Chae; Taeshik Earmme (Gels, 2024)
Polymerizable ionic liquid-based gel polymer electrolytes (PIL-GPEs) were developed for the first time using high-energy electron beam irradiation for high-performance lithium-ion batteries (LIBs). By incorporating an imidazolium-based ionic liquid (PIL) into the polymer network, PIL-GPEs achieved high ionic conductivity (1.90 mS cm−1 at 25 °C), a lithium transference number of 0.62, and an electrochemical stability exceeding 5 V. E-beam irradiation enabled rapid polymer network formation within a metal-cased battery structure, eliminating the need for initiators and improving the process efficiency. In the NCM811/PIL-GPE/Li cells, PIL-GPE (8:2) delivered an initial discharge capacity of 198.8 mAh g−1 with 82% retention at 100 cycles, demonstrating enhanced thermal stability and cycling performance compared to traditional GPEs. The demonstrated PIL-GPEs demonstrate strong potential for high-stability, high-performance LIB applications.